Brain insulin signalling, glucose metabolism and females' reproductive aging: A dangerous triad in Alzheimer's disease. (1st July 2018) - Duarte, A.I.; Santos, M.S.; Oliveira, C.R.; Moreira, P.I.
Abstract: Alzheimer's disease (AD) constitutes a major socioeconomic challenge due to its disabling features and the rise in prevalence (especially among (peri)menopausal women and type 2 diabetes patients). The precise etiopathogenesis of AD remains poorly understood. Importantly, its neurodegenerative perspective has been challenged towards a more "systemic" view. Amyloid-β (Aβ) and hyperphosphorylated Tau protein (P-Tau) (the main AD neuropathological features) affect and are affected by peripheral and brain insulin signalling dysfunction, leading to glucose dysmetabolism, synaptic loss and AD-related cognitive deficits. This may be anticipated and exacerbated by the progressive loss of estrogen (and interactions, e.g., with insulin) during females' aging, increasing their risk for AD, especially during menopause. Under this perspective, we aimed to discuss the recent findings (and controversies) behind the peripheral view of AD, and the role for insulin deficits and brain glucose dysmetabolism in such diseased brain. We also focused on the metabolic shift and the putative effects of gender (especially during midlife/perimenopause) herein. We finally discussed AD as the potential "type 3 diabetes", and the therapeutic potential of restoring brain insulin levels or glucose energy metabolism via administration of intranasal insulin and use of ketogenic diets. In sum, AD appears to lie on an intricate crosstalk between age-related metabolic, hormonal and specific genetic changes that challenge its traditional view. Hence, clarification of AD risk factors (besides aging and gender) and pathophysiological mechanisms will allow to establish accurate preventive strategies, biomarkers and more efficient drugs – all urgent medical needs in our increasingly aged societies. This article is part of the Special Issue entitled 'Metabolic Impairment as Risk Factors for Neurodegenerative Disorders.' Highlights: Aβ and P-Tau affect peripheral insulin secretion and glucose metabolism. Peripheral insulin reaches the brain, which may also synthesize its own hormone. AD affects brain and peripheral insulin function, replacing glucose use by ketones. Female gender anticipates and exacerbates these deleterious effects. Intranasal insulin and ketogenic diets may be therapeutically promising against AD.